Validation of inflammatory genetic variants associated with long-term cancer related fatigue in a large breast cancer cohort - Maurer, Tabea; Behrens, S.; Jung, A. Y.; Obi, N.; Thöne, K.; Schmidt, Martina; Becher, Heiko; Chang-Claude, Jenny (Brain, behavior and immunity, 2018)
Studies to date have reported several associations between single nucleotide polymorphisms (SNPs) and cancer related fatigue (CRF), but have been limited by small sample sizes, missing adjustment for relevant covariates or multiple testing, as well as varying CRF definitions, i.e. time and method of assessment. This study aimed to validate previously reported associations using the largest independent breast cancer sample to date and to evaluate further functional cytokine variants in relation to total CRF and all relevant CRF subdomains (physical, cognitive, and affective CRF).